A novel glycol sensor of silkworm excrement based microporous carbons (SEMCs)/SnO2 nanoparticles. (March 2023) - Xu, X.L.; Jiang, H.T.; Wang, X.P.; Wang, S.Y.; Liu, W.W.; Ma, W.; Wang, M.Y.; Ma, S.Y.
Abstract: In this paper, silkworm excrement are processed by carbonization and activation processing to innovatively prepare silkworm excrement based microporous carbons (SEMCs). The unique microporous SEMCs/SnO2 composite nanostructure then can be skillfully constructed. The characterizations of crystallinity, microstructure and morphology of SEMCs and SEMCs/SnO2 clearly show the polycrystalline nanostructure based on amorphous SEMCs and tetragonal rutile SnO2, which is composed of semiconductor microcrystals of small-sized SnO2 . The sensing properties of SEMCs/SnO2 composite sensor are studied by using static sensor test system. The prepared SEMCs/SnO2 sensor can effectively detect glycol with excellent sensing performances, including the high response value of 132, excellent selectivity and long-term stability. The hybridization process and the resulting numerous heterojunction interfaces originated from the biomass template of silkworm excrement may benefits the glycol sensing performance. Highlights: Biomass template of silkworm excrement are innovatively utilized for the facile synthesis of SEMCs/SnO2 nanoparticles. The SEMCs/SnO2 sensor presents excellent selectivity and detection limit of 4.8 ppb to glycol. The hybridization process and the resulting heterojunction interfaces may benefits the glycol sensing performance.